Applying Machine Learning Techniques to Identify Undiagnosed Patients with Exocrine Pancreatic Insufficiency - Bruce Pyenson; Maggie Alston; Jeffrey Gomberg; Feng Han; Nikhil Khandelwal; Motoharu Dei; Monica Son; Jaime Vora (Journal of Health Economics and Outcomes Research)
**Background:** Exocrine pancreatic insufficiency (EPI) is a serious condition characterized by a lack of functional exocrine pancreatic enzymes and the resultant inability to properly digest nutrients. EPI can be caused by a variety of disorders, including chronic pancreatitis, pancreatic cancer, and celiac disease. EPI remains underdiagnosed because of the nonspecific nature of clinical symptoms, lack of an ideal diagnostic test, and the inability to easily identify affected patients using administrative claims data.